The role of inventory optimization and organizational performance - Aliro Sandra Etalu (Uganda Christian University, 2024)
ABSTRACT This dissertation consists of five chapters, chapter one consists of introduction of the variables, their scopes and statement of the problem, general objectives, specific objectives, research questions and the scope of the study. Chapter two draws down the literature review, chapter three narrates the methods of data collection, populationsize, study population while chapter four and five crowns up with data analysis, discussing research findings, conclusions, recommendations and spot areas for further research. Introduction Inventory optimization is the process that aims to minimize the total cost of inventory while meeting while meeting customer demand and service levels The purpose of the study is to find out the role of inventory optimization and organizational performance. The objective of the study is to find out the role of inventory optimization and organizational performance. To find out the role of inventory storage on organizational performance To find out the role of demand forecasting on organizational performance To find the relationship between ABC analysis and organizational performance The scope of this study is restricted to the role of inventory optimization and organizational Methodology The methodology basically talks about the research design which was the cross sectional study design,study population, sample size,data collection methods, ethical consideration and dissemination of findings. Presentation of data analysis and interpretation This discusses the findings of the study, presentation of data, the gender composition of the respondents, age brackets of the respondents, academic background of the ABSTRACT This dissertation consists of five chapters, chapter one consists of introduction of the variables, their scopes and statement of the problem, general objectives, specific objectives, research questions and the scope of the study. Chapter two draws down the literature review, chapter three narrates the methods of data collection, populationsize, study population while chapter four and five crowns up with data analysis, discussing research findings, conclusions, recommendations and spot areas for further research. Introduction Inventory optimization is the process that aims to minimize the total cost of inventory while meeting while meeting customer demand and service levels The purpose of the study is to find out the role of inventory optimization and organizational performance. The objective of the study is to find out the role of inventory optimization and organizational performance. To find out the role of inventory storage on organizational performance To find out the role of demand forecasting on organizational performance To find the relationship between ABC analysis and organizational performance The scope of this study is restricted to the role of inventory optimization and organizational Methodology The methodology basically talks about the research design which was the cross sectional study design,study population, sample size,data collection methods, ethical consideration and dissemination of findings. Presentation of data analysis and interpretation This discusses the findings of the study, presentation of data, the gender composition of the respondents, age brackets of the respondents, academic background of the